Visualization of Epidermal and Dermal Alteration in Papulonodular Mucinosis by Multiphoton Microscopy. Issue 1 (11th June 2012) - Zhu, Xiaoqin; Lin, Lihang; Yu, Haibo; Zhuo, Shuangmu; Chen, Jianxin; Liu, Jingjing; Wang, Yuying
Summary Papulonodular mucinosis (PM) is a cutaneous clue to the presence and activity of silent lupus erythematosus (LE), but the exact pathogenesis is still under secret. Moreover, the currently available treatments for PM are not satisfactory. To demonstrate the possibility of multiphoton microscopy (MPM) to trace the pathological state of PM and evaluate the treatment efficacy, epidermal and dermal alteration in skin lesion with PM before and after treatment was examined using MPM. Microstructure of epidermis as well as content and distribution of collagen and elastin in dermis were quantified to characterize the pathological states of PM. The results showed significant morphological difference between skin lesion before and after treatment, indicating the possibility of MPM to assess the therapeutic efficacy. With the advancement on MPM miniaturization and enhancement of contrast and depth of imaging, the MPM technique can be applied in in vivo tracking PM formation and progression, and leading the better understanding the PM pathogenesis and mechanism of response to any treatment, helping to establish novel effective therapies for PM. SCANNING 35:22‐27, 2013. © 2012 Wiley Periodicals, Inc.